2019
DOI: 10.1016/j.alcohol.2018.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Daily factors driving daily substance use and chronic pain among older adults with HIV: An exploratory study using ecological momentary assessment

Abstract: Background: Adults 50 and older make up approximately 50% of persons living with HIV. Multiple co-morbidities are common among this group, including chronic pain and substance abuse, yet little is known about the daily factors that either enhance or inhibit these experiences or behaviors. This study explored daily drivers of substance use, pain, and relief from pain among older adults living with HIV utilizing ecological momentary assessment (EMA).Method: Participants (N=55), ages 49-71, completed seven consec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
3
8
0
Order By: Relevance
“…Opioids may be particularly lethal for even healthy OA whose aging renal system is unable to eliminate the drug efficiently from the body -thereby accumulating to toxic and/or lethal levels. A study of OA with HIV and chronic pain found a reciprocal relationship with daily alcohol consumption and daily reports of pain -each increasing the other [44], as is supported elsewhere in the literature [48].…”
Section: Painsupporting
confidence: 56%
See 2 more Smart Citations
“…Opioids may be particularly lethal for even healthy OA whose aging renal system is unable to eliminate the drug efficiently from the body -thereby accumulating to toxic and/or lethal levels. A study of OA with HIV and chronic pain found a reciprocal relationship with daily alcohol consumption and daily reports of pain -each increasing the other [44], as is supported elsewhere in the literature [48].…”
Section: Painsupporting
confidence: 56%
“…Another example relates to OA with HIV. About 17% of new cases of HIV are OA, and substance use is common among this population [44]. Complicated antiretroviral medication regimens for HIV could be rendered relatively inert due to substance use.…”
Section: Kuerbismentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that hazardous drinking was association with a 1-point mean increase in pain interference compared to those who did not report hazardous drinking, which is considered clinically significant in guidelines for clinical trial endpoints [ 44 ] and by other researchers [ 45 ]. This magnitude of effect is similar to that observed in the prior study by Larance et al [ 26 ] In addition, this study supports the findings of a recent study which examined relationships between substance use and pain among PLWH using ecologic momentary assessments [ 46 ]. In that study alcohol emerged as the only substance that had a reciprocal relationship with pain: heavier drinking predicted worse pain and worse pain predicted heavier drinking.…”
Section: Discussionsupporting
confidence: 90%
“…Yet, the magnitude of that effect was also smaller than for pain interference, and therefore results might not be considered of clinical significance even if found to be statistically significant in a larger sample. In addition, given the observational study design, we cannot presume causality; to date the literature suggests bi-directional relationships between alcohol use and pain among PLWH [ 43 , 46 ], which is consistent with the non-HIV focused literature [ 20 , 47 ]. We acknowledge that it is possible that greater pain interference could lead to more heavy drinking, as prior studies have demonstrated associations between pain and heavy alcohol use [ 17 ] and relapse risk [ 15 , 60 ].…”
Section: Discussionsupporting
confidence: 72%